Agave maria-patriciae (Polycephalae Group: Asparagaceae), a new species from Central Coastal Veracruz, Mexico - Arzaba-Villalba, Carlos; Cházaro-Basáñez, Miguel; Viveros-Colorado, César (Phytotaxa, 2018)
Agave maria-patriciae Cházaro & Arzaba is described and illustrated here as a new species from the central coast of the state of Veracruz in Mexico. It belongs to the subgenus Littaea and Polycephalae group, which contains tropical and subtropical species from the American continent. Agave maria-patriciae is closely related to A. pendula, but differs from the latter by having smaller rosettes, shorter and suberect stems and smaller and subsessile flowers. It is only known from a small population in the oak forest from the mountains of Sierra de Monte de Oro in the municipality of Alto Lucero in eastern Mexico.